Common Fixed Point Results for \((φ,ψ)\)-Weak Contraction Mappings via \(f\)-\(α\)-Admissible Mappings in Intuitionistic Fuzzy Metric Spaces - Onsod, Wudthichai; Kumam, Poom (Communications in Mathematics and Applications, 2016)
In this paper, by using the concept of \(f\)-\(α\)-admissible mappings, we prove common fixed point in intuitionistic fuzzy metric spaces. We also introduce the notion of \(f\)-\(α\)-\(φ\)-\(ψ\)-weak contraction mappings in intuitionistic fuzzy metric spaces. The presented theorems extend, generalize and improve the corresponding results which given in the literature.
Keywords: Common fixed point; Intuitionistic fuzzy metric space; \(α\)-admissible; \((φ; ψ)\)-weak contractions